The Role of Muscle Biopsy in Diagnostic Process of Infant Hypotonia: From Clinical Classification to the Genetic Outcome - Veneruso, Marco; Fiorillo, Chiara; Broda, Paolo; Baratto, Serena; Traverso, Monica; Donati, Alice; Savasta, Salvatore; Falsaperla, Raffaele; Mancardi, Maria Margherita; Pedemonte, Marina; Panicucci, Chiara; Piatelli, Gianluca; et al. (Frontiers in Neurology, 2021)
The role of muscle biopsy in the diagnostic work out of floppy infants is controversial. Musclesampling is invasive and often results are not specific. The rapid expansion of genetic approach has made the muscle histopathology analysis less crucial. This study aims to assess the role and efficacy of muscle histopathology in the diagnostic algorithm of hypotonia in early infancy through a retrospective analysis of 197 infants who underwent muscle biopsy in their first 18 months of life. Data analysis revealed that 92/197 (46,7%) of muscle biopsies resulted non-specific (80) or normal (12), not allowing a specific diagnosis. In 38/197 (20,8%) cases, biopsy suggested a metabolic or mitochondrial myopathy, while in 23/197 cases (11,7%), we found evidence of muscular dystrophy. In 19/197 cases (9,7%) histopathology characteristics of congenital myopathy were reported. In 21/197 cases (11,1%) the histopathological study indicated the presence of neurogenic damage. Overall, 43 diagnoses were then achieved by oriented genetic tests. Muscle biopsy results were consistent with genetic results in 90% of cases. Diagnostic algorithms for the diagnosis of a floppy infant are largely missing. Muscle biopsy alone can lead to a diagnosis, help the clinician in the choice of a genetic test or even modify a diagnosis made previously.